Investigating teachers’ pedagogical adaptations for effective technology integration in EFL classrooms - Marzuki, Abdul Gafur; Nur Aisiyiah, Vemmy Maidita; erizar, Erizar; Amalia, Ila; Huriyah, Huriyah; Triassanti, Risa; Kencanawati, Dewi (LP2M IAIN Sultan Amai Gorontalo, 2026)
Background: The rapid integration of digital technologies in secondary education has transformed English as a Foreign Language instruction, yet effective implementation remains uneven and highly contextual. While prior studies often focus on access or technological competence, less attention has been given to how teachers adapt pedagogically within real classroom conditions, particularly in regional Indonesian contexts. Aims: This study investigates how EFL teachers adapt their instructional practices in technology integrated classrooms, examining forms of implementation, contextual factors influencing adaptation, and teachers’ perceptions of instructional effectiveness. Methods: A qualitative multiple site case study was conducted at SMA Negeri 1 Palu and SMA Alkhairaat Palu in Central Sulawesi, Indonesia. Ten EFL teachers were selected through purposeful sampling. Data were collected through semi structured interviews and classroom observations between March and May 2025. The data were analyzed using thematic analysis following Braun and Clarke’s six phase framework, integrating inductive coding with theoretically informed interpretation. Results: The findings indicate that technology integration operates as a dynamic process of pedagogical negotiation rather than linear adoption. Teachers reorganized lesson structures, modified digital tasks in response to classroom contingencies, and recalibrated instructional decisions when facing infrastructural limitations. Professional experience influenced adaptive flexibility, with more experienced teachers demonstrating greater capacity for instructional redesign. Although digital tools enhanced student engagement, their effectiveness depended on deliberate scaffolding and pedagogical orchestration. Implications: This study advances a process-oriented understanding of pedagogical adaptation in technology-mediated EFL classrooms. The findings underscore the centrality of teacher agency and reflective judgment in sustaining meaningful digital learning environments. Professional development initiatives should therefore prioritize adaptive expertise and pedagogical reasoning rather than technical skill acquisition alone.